Rhipicephalus microplus cystatin as a potential cross-protective tick vaccine against Rhipicephalus appendiculatus - Parizi, Luís Fernando; Rangel, Carolina Konrdörfer; Sabadin, Gabriela Alves; Saggin, Bianca Fagundes; Kiio, Irene; Xavier, Marina Amaral; da Silva Matos, Renata [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Seixas, Adriana; Konnai, Satoru; Ohashi, Kazuhiko; Githaka, Naftaly Wang'ombe; et al. (Elsevier, 2020)
Rhipicephalus appendiculatus, the brown ear tick, is an important disease vector of livestock in eastern, central and southern Africa. Rhipicephalus appendiculatus acaricide resistance requires the search for alternative methods for its control. Cystatins constitute a superfamily of cysteine peptidase inhibitors vital for tick blood feeding and development. These inhibitors were proposed as antigens in anti-tick vaccines. In this work, we applied structural and biochemical approaches to characterize a new cystatin named R. appendiculatus cystatin 2a (Racys2a). Structural modeling showed that this new protein possesses characteristic type 2 cystatin motifs, besides conservation of other structural patterns along the protein. Peptidase inhibitory assays with recombinant Racys2a showed modulation of tick and host cathepsins involved in blood digestion and immune system responses, respectively. A heterologous tick challenge with R. appendiculatus in rabbits immunized with recombinant Rhipicephalus microplus cystatin 2c (rBmcys2c) was performed to determine cross-reactivity. Histological staining showed that rBmcys2c vaccination caused damage to the gut, salivary gland and ovary tissues in R. appendiculatus. Furthermore, cystatin vaccine reduced the number of fully engorged adult females in 11.5 %. Consequently, strategies to increase the protection rate are necessary, including the selection of two or more antigens to compose a vaccine cocktail.
Keywords: Parasite; Peptidase inhibitor; Vaccination